Ocena sanacije proizvodnih družb slovenskih železarn v obdobju 1993-1997 - Vodopivec, Franc (Kovine zlitine tehnologije, 1999)
Figures on the operation of production companies providing for more than 90% of the income and 100% of the export are presented and discussed. Improvement was achieved by the sales value per capital and in the average price of sales. Finansing expenses exceeded the expected profit in the whole restructuring period. The balance sheet by the end of 1997 shows wery great short time habilities. In the restructuring period investment expenses were very low.
Keywords: proizvodnja jekla; predelava jekla; prodaja; izvoz; sanacija; stroški; financiranje; investicije